Influence of attachments on the efficiency of molar distalization using clear aligners – An updated systematic review - Harsha.L; Nivethigaa Balakrishnan; Saravana Dinesh S P; Arya S Prasad (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: With the advent of intra oral scanning, virtual treatment planning and 3D printing, the field of orthodontics has grown beyond limits. With increasing demand for invisible orthodontic treatment, clear aligners have set a mark in providing efficient orthodontic tooth movements. Several clinical studies have been published, especially in the last decade to justify the same. Efficiency of various tooth movements with clear aligners has also been extensively studied. One of the most challenging tooth movements with clear aligners is molar distalization. The distalization for maxillary molars is needed to correct non extraction patterned class 2 malocclusions. Several studies have extensively studied the same however a sound clinical judgment is required on the basis of high level of evidence. Objective: The objective of this systematic review was to systematically search the literature and assess the available evidence regarding the effectiveness of clear aligners in bringing about molar distalization with or without attachments. Search Strategy: An electronic database search of published and unpublished literature in english was performed till April 2021 in the following databases: Google scholar, PUBMED,TRIP, LILAC, Web of science and Cochrane databases. The reference list of all the eligible articles were examined for additional studies. Articles were selected based on selection criteria. Reporting of this review was based on the Preferred reporting items for systematic review and meta-analysis (PRISMA) guidelines. Selection Criteria: All prospective/retrospective clinical studies on subjects/patients treated with clear aligners to achieve molar distalization with or without attachments were included in this Systematic Review. Data Collection And Analysis: Data extraction from the included articles was done by the authors independently.Data characteristics were extracted using data collection forms whereas the quality of the study was assessed using the Cochrane Risk of bias tool for randomized control trials and NewCastle Ottawa scale for non randomized control trials. Results: A total of 5 articles were included in this review. The amount of molar distalization reported was 2- 3mm. Conclusion: Of the five studies included, all the studies reported significant amounts of distalization. 3 retrospective studies concluded that distalization with aligners is the most effective of all tooth movements. One study concluded that aligners effectively achieved distalization of 2-3mm with efficacy of 87%, two other studies concluded that aligners effectively distalized the molars when tooth movement was performed using attachments, with good control over vertical dimension, and mesio-distal tipping.